1977
DOI: 10.1161/01.res.40.2.150
|View full text |Cite
|
Sign up to set email alerts
|

Change in liver blood flow and blood content in dogs during direct and reflex alteration of hepatic sympathetic nerve activity.

Abstract: SUMMARY A mean decrease of 60% in liver blood volume was recorded by a plethysmographic technique during electrical stimulation of the hepatic nerves in anesthetized, vagotomized dogs. A decrease in pressure in the vascularly isolated carotid sinus to 40 mm Hg, from a mean control of 144 mm Hg, decreased liver blood volume by a mean of 16%; arterial blood pressure increased by a mean of 77 mm Hg. Carotid sini's hypotension was accompanied by respective mean increases of 16% and 1.4% in hepatic arterial and por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…Studies in vivo indicate that there is intrinsic vasomotor tone in the portal vein (Johansson & Ljung, 1967) and that carotid sinus baroreceptors and noradrenaline have sizeable effects on portal venous tone (Alexander, 1954 ;Brooksby & Donald, 1971;Auden & Donald, 1975;Carneiro & Donald, 1977;Richardson & Withrington, 1978 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in vivo indicate that there is intrinsic vasomotor tone in the portal vein (Johansson & Ljung, 1967) and that carotid sinus baroreceptors and noradrenaline have sizeable effects on portal venous tone (Alexander, 1954 ;Brooksby & Donald, 1971;Auden & Donald, 1975;Carneiro & Donald, 1977;Richardson & Withrington, 1978 …”
Section: Discussionmentioning
confidence: 99%
“…The portal circulation has an important capacitance function (Brooksby & Donald, 1971;Mitzner & Goldberg, 1975;Carneiro & Donald, 1977;Donald, 1981). Little is known, however, of the capacitance characteristics of the large extra-hepatic vessels such as the portal vein.…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of venous capacitance by sympathetic outflow has been demonstrated with studies during electrical stimulation, including splanchnic and hepatic nerves (5,7), changes in carotid artery pressure (31), and pharmacological manipulation of sympathetic activity (23). The control of vascular capacitance by the carotid baroreflex has been well-investigated and demonstrated (30).…”
mentioning
confidence: 99%
“…It can be concluded that the effects, if any, of an increase in the catecholamine concentration in the blood on the hepatic circulation were physiologically too weak to be detected. CARNEIRO and DONALD (1977) reported that in the case of reflex hypertension caused by exposing the carotid sinus to local hypotension in dogs, HAF and PVF increased to 116 and 101.4% of the control, respectively. In our study, the maximum increase of HAF and PVF were obtained at the later and initial stages of SPEP, respectively.…”
Section: Effects Of Functional Exclusion Of Adrenal Glandsmentioning
confidence: 99%
“…TAKEUCHI, N. TERADA, and S. KOYAMA but the HAF shows ambiguous results: decreases (SELKURT and BRECHER, 1956;GALINDO, 1965;MUNDSCHAU et al, 1966) or increases (SANCETTA, 1953;GREENWAY et al, 1967b). Concerning the influence of reflexes on hepatic hemodynamics, occlusion of the carotid arteries in cats causes systemic arterial pressure (SAP) rise with little change in HAF (GREENWAY et al, 1967a), and carotid sinus hypotension in dogs increases the HAF and PVF (CARNEIRO and DONALD, 1977). Studies have been already made on the hemodynamics of the cutaneous, renal, intestinal, and skeletal muscle vascular beds TAKEUCHI and MIYAKAWA, 1980) and of blood mobilization from the renal, hepatic, jejunal, skeletal-muscle, and hind-paw vascular beds during blood pressure oscillation caused by the side pressure exertion procedure (SPEP).…”
mentioning
confidence: 99%